Moving the silence : a dialogue between art and spirituality - Goria, Gabrielle (My University, 2013)
This work illustrates the research I have conducted throughout the two years of my Master's degree programme in Theatre Pedagogy at the Theatre Academy of Helsinki (TeaK) on the topic of “active” silence: a quiet dimension of being, calm but not passive, characterized by a high level of awareness, openness and concentration at the same time. In March 2012 I led a one-day workshop with the title “Living the Silence” in seven different environments (among them: a school, two monasteries and a Theatre Academy), where I explored many possible combinations of art and meditation, in order to understand how the participants experienced “active” silence. In November 2012 I further developed my previous research on “active” silence by leading a two week-workshop, “Moving the Silence”, attempting to understand how I could develop a dialogue between different disciplines related to the practice of active silence such as meditation, T'ai Chi Ch'üan (the Chinese “Supreme Polarity boxing”) and expressive movement, without use of speech. The workshop led spontaneously towards a performance with the same title “Moving the Silence”, where I have been exploring the boundaries between meditation and performance, questioning how meditation can be a performance and vice-versa. We performed in February 2013. Silence proved to be a fruitful ground for a dialogue between art and spirituality, becoming a generative platform for developing meditative ways of working in the field of art. This thesis provides a detailed description of this work and the development of my personal conceptions about teaching.
Keywords: Silence.; Meditation.; Yoga.; Spirituality.; Vipassanā (Buddhism); Zen.; Tʻai chi chʻüan.; Qi gong.; hiljaisuus; mietiskely; jooga; spiritualiteetti; taiji; qi gong; Costa, Orazio.; tystnad; meditation; yoga; spiritualitet; taiji; qigong; fi=teatteriopettaja|sv=teaterpedagogik|en=Theatre Pedagogy|